PENGUKURAN INDEPENDENSI BANK INDONESIA SELAMA COVID-19 - Inda Fresti Puspitasari; Dhany Efita Sari; Siti Masitoh (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
Central bank independence in Indonesia has been regulated in UU No. 33 Year 2004 concerning amendements to UU No. 23 Year 2009 concerning Bank Indonesia. However, the central bank often got intervention in formulating its policies. During the pandemic covid-19 crisis, there were several attempts to intervene Bank Indonesia, such as the idea to form a Monetary Council, suggestions to allow BI Governors from politicians, and Perppu No. 1 Year 2020 which is allow BI to bought SUN in the primary market. Therefore, this study aims to measure the independence index of the central bank in Indonesia during 2007-2020 using the measurement method developed by Cukierman et al. (1994) to analyze the independence of Bank Indonesia during the covid-19 pandemic. The result of this study proves that BI independence index during the pandemic has decreased when compared to the pre-pandemic period. This study also proves that Bank Indonesia still needs to maintain its independence from all political attention, so its accountability and credibility of the monetary policy still can assured